Australia : Background Material. (IMF Staff Country Reports; Country Report, 1995)
This paper describes the developments in the Australian labor market during the 1990s. In 1994, a number of new labor market programs were launched, directed especially at the long-term unemployed, and a further step was taken in the evolutionary reform of the industrial relations system. The paper reviews developments in employment, wages, and productivity in Australia that formed the background to these policy initiatives. It also examines the conduct of fiscal policy at the Commonwealth and consolidated government levels and describes the fiscal consolidation strategy announced by the Commonwealth government for 1994/95-1997/98.